IMPROVING THE QUALITY OF EDUCATION AND PROFESSIONALISM OF TEACHERS THROUGH LESSON STUDY - Fatikhatun Najikhah; Wawan Shokib Rondli; Haryati Haryati; Dewi Astuti; Suningsih Suningsih (Jurnal Scientia, 2023)
This journal article will discuss Lesson Study as a gateway to improving the quality of education and teacher professionalism. Through a literature review and case studies, this article will discuss the concept of Lesson Study, how it is implemented in improving the quality of education and teacher professionalism, and the challenges and opportunities faced in implementing Lesson Study in Indonesia. The research method used in this journal article is a qualitative method with a library research approach. A literature study is carried out by searching for articles and books relevant to Lesson Study as a gateway to improving the quality of education and teacher professionalism. Searches were made through Google Scholar, ProQuest, and EBSCO search engines. Based on the discussion above, it can be concluded that Lesson Study is an alternative to developing the teaching profession through collaborative and sustainable activities. The principle of collaboration will facilitate teachers to build an effective and efficient learning community. In contrast, the sustainability principle will provide teachers opportunities to become a lifelong learning community. Implementing LS on an ongoing basis will help teachers develop professional competence and accelerate education quality improvement.